Study for Mainstreaming Environmental and Climate Change Policy On The Development Planning Agenda in Indonesia - Haryanto, Joko Tri; Nurkholis, Akhmad (Badan kebijakan Fiskal, 2014)
Over the past few years, environmental issues have became a major policy agenda in developed and developing countries. The government has some alternative policies that can be used as a form of the intervention either to play the role of market-based policies and government regulations as well as other options. In this context, the Government of Indonesia already issued Presidential Decree No. 61 Year 2011 on National Action Plan for Reducing Greenhouse Gas Emissions (RAN-GRK). Based on this document, financial source for climate change (PI) and also protection, preservation of the environment (PPLH) mainly comes from the state budget, local budget, private sector, and other sources legalized by regulations. Unfortunately, the capacity for this obligation is still constrained. For this reason, public funding must be able to cooperate with the private fundingr in order to leverage the capacity. Regarding this matter, the flexibility for the allocation of state budget/local budget is not easy, due several reasons. One of that reason is the lack of policy meanstreaming PPLH the PI on the budgeting systems, the nature of the management PI and PPLH and also lack of awareness from many stakeholders. By using descriptive analysis method, this paper tries to answer these issues from the variety of scenarios, especially in the sphere of government planning and budgeting policy.